Corporate Factors Affecting Carbon Disclosure for SDG 13 in Indonesia - Ihza Mahendra, Moch. Yusril; Lating, Ade Irma Suryani; Aripratiwi, Ratna Anggraini; Nufaisa, Nufaisa (Journal of Accounting Science, 2025)
General Background: Climate change, characterised by rising global temperatures, is a critical threat to sustainable development worldwide. Specific Background: In line with Sustainable Development Goal (SDG) 13 (Climate Action), disclosure of carbon emissions is increasingly vital. Knowledge Gap: Despite the increasing emphasis on ESG reporting, there are still significant gaps in the specificity and consistency of carbon emissions disclosure among Indonesian companies. Objective: This study aims to analyse the impact of environmental performance, firm size, and financial distress on carbon emissions disclosure, with corporate governance measured through the proportion of independent commissioners as a moderator variable. Methods: Using a quantitative-causal research design, this study utilises secondary data from 47 energy sector companies listed on the Indonesia Stock Exchange between 2021 and 2023, with 141 firm-year observations. Data was analysed using Regression Analysis of Moderation (ARM). Results: The findings show that environmental performance and firm size have a positive influence on carbon emissions disclosure, while financial distress has a negative effect. Corporate governance moderates the relationship between environmental performance and disclosure, by weakening the relationship. Novelty: This study uniquely integrates the triple bottom line framework with advanced financial ratios and governance factors. Implications: The results of this study provide valuable insights for policymakers and investors to improve transparency and accountability in achieving Indonesia's climate commitments.